Disinfection effect of adding slightly acidic electrolyzed water to artificial seawater under the condition of static hybrid - Wang, Chunfang; Huang, Xiaoling; Wang, Shuo; Yu, Yong; Zhu, Songming; Ye, Zhangying (International Journal of Agricultural and Biological Engineering, 2020)
Mixed solution of slightly acidic electrolyzed water (SAEW) and artificial seawater was used to investigate the disinfection potential of SAEW in artificial seawater. Inoculated Vibrio parahaemolyticus (suspended in 3% sodium chloride alkaline peptone water and 0.85% sodium chloride water, respectively) was subjected to different mixed-SAEW and SAEW immersion treatments (5-20 mg/L available chlorine concentration (ACC)). In the presence of organic matter, 4.07 logCFU/mL significant reduction (p<0.05) was achieved after treating with 20 mg/L mixed-SAEW for 15 min. There was 5.13 logCFU/mL reduction after treating with 15 mg/L SAEW for 15 min. For V. parahaemolyticus suspended in 0.85% sodium chloride solution, it was undetected after 30 s SAEW treatment (5 mg/L ACC) or 120 s mixed-SAEW treatment (10 mg/L ACC). At a ratio of SAEW and artificial seawater at 1:15 (V/V), SAEW could inactivate V. parahaemolyticus to undetectable level in artificial seawater in one minute, which was comparable with UV treatment of 10 W. The results indicated high sanitization potential of SAEW against V. parahaemolyticus in aquaculture seawater.Keywords: slightly acidic electrolyzed water, disinfection, inactivation, Vibrio parahaemolyticus, artificial seawater, ultravioletDOI: 10.25165/j.ijabe.20201302.4194Citation: Wang C F, Huang X L, Wang S, Yu Y, Zhu S M, Ye Z Y. Disinfection effect of adding slightly acidic electrolyzed water to artificial seawater under the condition of static hybrid. Int J Agric & Biol Eng, 2020; 13(2): 218–222.